Online Teaching and Learning in the COVID-19 Era Perspectives on Equity and Epistemic Justice - Maringe, Felix; Chiramba, Otilia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines the ongoing changes initially caused by the COVID-19 pandemic and the future prospects of teaching and learning in higher education institutions. It focuses on the impact of online education on issues of learning equity and epistemic justice. The transition from traditional face-to-face teaching to remote learning has exacerbated existing inequalities in epistemological access among higher education students, despite the shortcomings of the former in this regard. The book features essays by African academics who reflect on the challenges of epistemological access during the sudden shift to hybrid, blended and remote teaching and learning. It specifically explores the question of equitable learning in diverse home contexts, drawing on both theoretical and empirical studies conducted by the authors in South African universities and the region. The chapters employ the conceptual framework of epistemic injustice to define and explore various forms of such injustice, providing a basis for analyzing the implications of the transition to online pedagogy. Felix Maringe is Professor in Higher Education and Leadership at the University of Kigali, Rwanda. Otilia Fortunate Chiramba is a research fellow at the University of Johannesburg, South Africa.
1. Rethinking Hybrid Teaching in the South African Higher Education System: Promoting Equity and Epistemic Justice -- 2. Digital Education Ecosystem to Achieve Instructional Equity & Cognitive Justice -- 3. Streaming Content Online and Supporting Initial Teacher Educators During Covid-19 Pandemic -- 4. The Imperatives for Disadvantaged Students Support in He in the Covid-19 and Post Covid-19 Era -- 5. Psychological Barriers on Adjustment to Online Teaching and Learning in Universities During Covid-19 Pandemic: a Social Justice Perspective -- 6. Digital Revolution in Higher Education in the Covid-19 and Post Covid-19 Era -- 7. An Analysis of Covid-19 Related Factors That Affect the Girl-child's Access and Participation in Education -- 8. Managing Change From Face-to-face to Online Teaching and Learning in Higher Education During the Covid-19 Pandemic: Implications for Equity and Epistemic Justice -- 9. Protective Factors for Adjustment to Online Teaching During Covid-19 Pandemic: A Social Justice Perspective -- 10. Teaching and Learning in Higher Education in the Post-covid-19 Era: A Prospective View.
Keywords: Teachers -- Training of; Learning, Psychology of; Social justice; Education, Higher; Teaching and Teacher Education; Learning Theory; Social Justice; Higher Education